Reforming the MRI system: the Israeli National Program to shorten waiting times and increase efficiency - Noga Boldor; Sharona Vaknin; Vicki Myers; Nina Hakak; Michel Somekh; Rachel Wilf-Miron; Osnat Luxenburg (BMC, 2021)
Abstract Background Long waiting times (WT) for Magnetic Resonance Imaging (MRI) are a challenge in many countries and demand is forecast to increase with ageing populations. Since MRI is essential for diagnosis in numerous medical conditions, timely performance is of the utmost importance. Objective To describe the multi-faceted program developed by the Israel Ministry of Health (MoH) to shorten WT for MRI and increase efficiency, and to examine lessons that can be learned for other health systems. Data sources Data were obtained from the Israel MoH from 2015-2019. Methods The plan used multiple strategies and comprised the following elements: providing additional scanners, dedicating additional personnel to MRI units, maximizing efficiency, establishing a training program for radiographers and a fellowship program for radiologists, introducing financial incentives to health maintenance organizations and implementing a computerized monitoring system. Results A substantial reduction in mean WT was demonstrated, from 52 days in 2015, to 24 days in 2016 and 2017. This was followed by a slight increase to 26 and 32 days in 2018 and 2019, respectively. The relative decline in WT from 2015 to 2019 was 38.5%. The number of scanners doubled during this period while the number of radiographers and radiologists with formal MRI training increased. Conclusions The broad scope of this comprehensive reform was successful in addressing long WT and improving care provision from a wide perspective: economic, workforce and infrastructure. Bottlenecks in the MRI system cannot be addressed from a single angle, rather requiring a whole system approach.